Environmental Awareness Assistance Based on Islamic Religious Education with a Gender Perspective for the Coastal Communities of the Musi River, Palembang - Wigati, Indah; Yuniar, Yuniar; Lestari, Weni (Amalee: Indonesian Journal of Community Research and Engagement, 2025)
The Musi River plays an important role in the people's economy on its coast. However, the usefulness of this river is not accompanied by public awareness of environmental preservation. The environment on the coast of this river is polluted by waste or garbage. The purpose of the assistance is to increase environmental awareness based on Islamic Religious Education from a gender perspective for the Musi River, Palembang, and coastal communities. The assistance method used is Asset Based Communities Development (ABCD). The subjects of assistance were 53 people from the coastal communities of the Musi River in Palembang. Data was collected through observation, interviews, documentation, and questionnaires. Assistance was carried out through socialization based on Islamic Religious Education integrated with ecological values from a gender perspective. Data analysis used qualitative and Rasch analysis. The assistance results showed that the Musi River's coastal assets in Palembang are locations and human resources that have a high spirit of mutual cooperation to preserve the environment. Rasch's analysis of the level of understanding of environmental awareness based on Islamic religious education from a gender perspective showed that 31 people were categorized as very high, six people were high, 16 people were moderate, and no one was categorized as low. Religious values about nature as a trust in God, the importance of maintaining cleanliness, and the prohibition of causing damage to the earth are the main foundations in building environmental awareness. Gender roles can maximize the participation of men and women in environmental conservation efforts